SPECIFICS OF TRANSLATING EMOTIONAL AND AESTHETIC INFORMATION MARKERS - I. Makhova; O. Chudnova (Гуманитарные и юридические исследования)
This article analyzes the major ways for translating emotional and aesthetic information lexical markers in the framework of maintaining the perlocutive effect of a psychologized text. Within the analysis, the extremely psychologized memoir-autobiographical text is viewed as a literary memory of events from the past created by a participant of the events that are described. Currently, such works are analyzed in history, in philology, as well as in psychology, and sociology as an important source of information. A comprehensive analysis expands the informational capacity of memoir-autobiographical texts, which leads to the development of more effective strategies for the emotivization of the target text. Following the aim and objectives of the undertaken research, the specifics of the translation of various lexical-stylistic means of emotional influence (based on F. Fenelon's autobiography) was revealed. Stylistically neutral vocabulary allows highlighting emotional means as a way to create a stylistic coloring. Emotionally colored words and expressions allow the author of the source and translation to describe the intolerable living conditions that prisoners had to suffer in a concentration camp, at the same time helping get distracted from from the current situation and translating sensory-somatic heteroimages into reflexive auto-images meant to set the recipient to perceiving the text within the framework of the immanently given "action scheme". While maintaining the stylistic specifics in the translation for the most complete transfer of all of the author's feelings and emotions, the most effective is the use of vocabulary equivalents, and in case they are lacking, more effective is the use of stylistic neutralization to follow the principle of gender specification. The study outcomes help broaden the understanding of the ways for emotivization and psychologization of the memoir-autobiographical text, and continue studying and developing basic principles for translation of psycho-emotive space in view of not only linguocultural specifics, yet also the speaker-recipient focus.